Viable model of creative company for small and medium art crafts enterprises (Nexo Revista Científica, 2021)
Indigenous artisan companies in Mexico, face difficulties in coordinating and systematizing their design processes and dealing with imported handicrafts. After critical review of product design methodologies, based on the Viable Systems Model approach and applying the Soft Systems Methodology through semi-structured interviews and participatory action research; A Viable Model for a Creative Enterprise is proposed to improve the adaptability of these companies with emphasis on the systems identified as relevant for design management. The results are a reference and diagnostic framework for small and medium enterprises that wish to improve their systemic viability by incorporating design management into their operational processes.